Form for reporting Iowa Christmas bird counts to Iowa Bird Life, J. Donald Gillaspey, December 26, 1987 - Gillaspey, J. Donaldet al (1987)
Iowa Christmas bird counts of regular and uncommon species found in Lamoni contributed by J. Donald Gillaspey, December 26, 1987. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1987-1988. Epson - sheet feed